Cost-Effective Analysis (AEB) of Antiretroviral (ARV) Use of TLD and TLE in Outpatient HIV Patients - Kurniadi Rafindra, Meidi; Andriani, Medi; Dewi, Rasmala (Jurnal Multidisiplin Indonesia, 2025)
Antiretroviral treatment is one of the biggest parts of the treatment for people infected with HIV. This study aims to determine the effectiveness of drugs and the cost efficiency of ARV combination drug therapy. The study used a non-experimental research design that was observational to determine the Cost Effectiveness Analysis of 2 combinations of ARVs, namely the combination of TLD (Tenofovir + Lamivudin + Dolutegraph), and the combination of TLE (Tenofovir + Lamivudin + Efavirenz). Data collection was carried out retrospectively from the medical record data of patients who started ARV treatment in the period 2021 to 2023. Total of 189 patients were actively treated as outpatients at VCT polyclinics and 64 who met the inclusion criteria were used as study subjects. The effectiveness of treatment uses the parameters of the Viral Load test results. Treatment is said to be effective if the Viral Load test result is <40 copies/mL. Based on the results of the Viral Load test, the TLD combination was more effective (75.9%) compared to the TLE combination (66.7%). Based on Cost Effective Analysis, the combination of TLD (Tenofovir + Lamivudin + Dolutegrafir) is better with an ACER value of IDR 39,871 compared to the combination of TLE (Tenofovir + Lamivudin + Efavirenz) with an ACER value of IDR 68,599.